PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PT. KARYA PUTRA GRAFIKA) - Nurtika Meinitasari; Chaerudin (MANAJEMEN DEWANTARA, 2023)
PT. Karya Putra Graphic which is engaged in the restaurant, hotel, outbound, catering, printing and education consulting businesses in recent years has experienced declining performance. The findings from the initial observations are the low discipline of the employees due to the low sense of responsibility towards work. Therefore, this study aims to examine what factors influence the level of employee performance. The method used in this study is a quantitative research method with an associative approach. Data was collected using a questionnaire instrument which was distributed to all employees who met 114 people. Furthermore, the data will be processed using path analysis with the help of SPSS. The research results show that motivation and discipline have a positive and significant relationship. In addition, both also have a significant influence on employee performance either partially or simultaneously